(untitled) (Journal of Partial Differential Equations, 1995)
This paper is devoted to the study of tho least-energy solutions of a singularly perturbed Neumann problem involving critical Sobolev exponents. The condensation rate is given when n > 4 apd an asymptotic behavior result is obtained.